2011
DOI: 10.1080/13554794.2010.532138
|View full text |Cite
|
Sign up to set email alerts
|

Impaired event memory and recollection in a case of developmental amnesia

Abstract: A current debate in the literature is whether all declarative memories and associated memory processes rely on the same neural substrate. Here, we show that H.C., a developmental amnesic person with selective bilateral hippocampal volume loss, has a mild deficit in personal episodic memory, and a more pronounced deficit in public event memory; semantic memory for personal and general knowledge was unimpaired. This was accompanied by a subtle difference in impairment between recollection and familiarity on lab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 65 publications
4
60
1
Order By: Relevance
“…In particular they lacked contextual details and the subjective feeling of reliving. In contrast to his performance on various anterograde explicit memory tests, his old semantic knowledge was good, which suggests a use of compensatory strategies (Rosenbaum et al, 2011). His performance on free recall was worse than that on recognition which is consistent with findings from patients with developmental amnesia (Adlam et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In particular they lacked contextual details and the subjective feeling of reliving. In contrast to his performance on various anterograde explicit memory tests, his old semantic knowledge was good, which suggests a use of compensatory strategies (Rosenbaum et al, 2011). His performance on free recall was worse than that on recognition which is consistent with findings from patients with developmental amnesia (Adlam et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…One potentially intriguing result in our study is the reduction in the amygdala gray matter, when using a less conservative statistical threshold. The lack of reports of amygdala gray matter reductions in previous studies might be accounted for by the statistical threshold applied and/or the fact that apart from hippocampal formation, other medio-temporal lobe regions did not undergo rigorous volumetric quantifications Rosenbaum et al, 2011). In line with other studies showing damage to thalamic areas after episodes of (perinatal) hypoxia (Jacob and Pyrkosch, 1951;Voit et al, 1987;Markowitsch et al, 1997;Cowan et al, 2003;Macey et al, 2005;de Haan et al, 2006), we identified indices of reductions in gray matter density in thalamus, namely in the pulvinar, when we applied a less conservative statistical threshold (p < 0.001, uncorrected).…”
Section: Discussionmentioning
confidence: 92%
“…Her memory retrieval nevertheless benefits from repetition when repeated items in a study list are spaced rather than presented in immediate succession (Green et al, 2014), an effect that has also been demonstrated in Korsakoff patients (Cermak et al, 1996). Areas of cognitive function that had not undergone rigorous investigation in developmental amnesia until H.C. include memory for public events, which was found to be impaired (Rosenbaum et al, 2011;see Maguire et al (2001) for initial findings of intact public event memory in Jon), and the ability to hold information online in working memory, which was intact for famous faces and known vocabulary but impaired when the information was previously novel (Rose et al, 2012;see Allen et al (2014) and Baddeley et al (2011) for complementary evidence in Jon). Mental state inference on standard tests of theory of mind was found to be intact (Rabin et al, 2012), consistent with an average sized social network (Davidson et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…We have identified such an instance in a young woman, H.C., who shares a partially overlapping behavioral profile with other developmental amnesic cases. Like other cases of developmental amnesia, H.C. has selectively impaired episodic memory (Rosenbaum et al, 2011). A parallel pattern of worse recollection than familiarity of recognized items was observed on laboratory tests of episodic memory.…”
Section: Introductionmentioning
confidence: 97%
“…Here, we tested an amnesic individual (HC) with documented bilateral lesions of the hippocampus and connected subcortical structures, but intact PrC (Olsen et al, 2013;Rosenbaum et al, 2015). HC is known to exhibit deficits in episodic recollection of autobiographical lifetime experiences (Kwan, Carson, Addis, & Rosenbaum, 2010;Rabin, Carson, Gilboa, Stuss, & Rosenbaum, 2012;Rosenbaum et al, 2011). Given that lesions limited to the hippocampus, or the extended hippocampal system, can spare item familiarity with reference to recent laboratory exposure, we asked whether such a lesion could also spare the assessment of cumulative lifetime familiarity of Running Head: Medial Temporal Lobes and Familiarity Impairments 9 object concepts.…”
Section: Introductionmentioning
confidence: 98%